CAREER GUIDANCE FOR WOMAN AFTER PARENTAL LEAVE - Rubuļņika, Līga (Education Reform: Education Content Research and Implementation Problems, 2022)
Often, the return of woman to work after parental leave gives many reflections and emotional experiences on how to reconcile the balance between work and private life. Becomes important still woman, after long absences, is able to compete qualitatively on the labor market.The mother's competencies, professional knowledge, qualifications and compliance with job responsibilities and requirements are important in order to be able to adapt to new social roles.Fundamentally, whether and to what extent, woman needs career support.The mission of a career counselor in a conversation with a mother after parental leave is to guide her to possible strategies for action. It is important to raise a woman's awareness of her desires, skills, strengths, opportunities for her success in her career development. The study, on career support for mothers after parental leave, involved 190 mothers who answered 40 questionnaire questions. The study was conducted with the aim of clarifying how existing career support can help mothers to return to the labor market after parental leave. The results of the study show that most mothers need career support after parental leave. Career support would be more demanding if information on career support services was available in one place for this target group. The most frequently mentioned troublesome conditions for career development are work and private life disbalance, lack of time, unavailability of childcare services, finance.